1997
DOI: 10.1124/mol.51.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a Thrombin Receptor Tethered Ligand Analogue to Human Platelet Thrombin Receptor

Abstract: A thrombin receptor-radioligand binding assay was developed using [3H]A(pF-F)R(ChA)(hR)Y-NH2 ([3H]haTRAP), a high affinity thrombin receptor-activating peptide (TRAP), and human platelet membranes. Scatchard analysis of saturation binding data indicated that [3H]haTRAP bound to platelet membranes with a Kd of 15 nM and a Bmax of 5.2 pmol/mg of protein. The binding was reduced by GPPNHP, a nonmetabolizable GTP analogue. Various TRAPs and a TRAP antagonist, but not other receptor agonists, displaced [3H]haTRAP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Expression of CD62 and CD63 on washed human platelets were quantified by flow cytometry using FITC-labeled CD63 antibody (Immunotech, Beckman Coulter Co., Fullerton, CA) and phycoerythrin-labeled CD62 antibody (BD Biosciences) as described previously (5). PAR-1 cleavage at Arg 41 -Ser 42 and release of PAR-1 activation peptide, PAR-1-(1-41), in the supernatants of washed platelets was quantified by an ELISA as described previously (16). PAR-4 cleavage at Arg 47 -Gly 48 was also measured by an ELISA as the release of PAR-4-(1-47) as described below.…”
Section: Affinity Purified Chicken Anti-human Par-1-(35-62)-igy (Antimentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of CD62 and CD63 on washed human platelets were quantified by flow cytometry using FITC-labeled CD63 antibody (Immunotech, Beckman Coulter Co., Fullerton, CA) and phycoerythrin-labeled CD62 antibody (BD Biosciences) as described previously (5). PAR-1 cleavage at Arg 41 -Ser 42 and release of PAR-1 activation peptide, PAR-1-(1-41), in the supernatants of washed platelets was quantified by an ELISA as described previously (16). PAR-4 cleavage at Arg 47 -Gly 48 was also measured by an ELISA as the release of PAR-4-(1-47) as described below.…”
Section: Affinity Purified Chicken Anti-human Par-1-(35-62)-igy (Antimentioning
confidence: 99%
“…Activation of human platelet PAR-1 arising from cleavage at Arg 41 -Ser 42 in response to ␣-thrombin and the simultaneous exposure of the previously cryptic tethered ligand domain (beginning with the sequence 42 SFLLRN), were first reported by Vu and colleagues (4). Two studies have confirmed cleavage at Arg 41 -Ser 42 by quantifying platelet PAR-1 activation peptide release (5,6). Monoclonal antibodies directed against the hirudin-like ␣-thrombin-binding domain of PAR-1 or against residues spanning the reported ␣-thrombin cleavage site (PAR-1 span antibodies) practically eliminated all responses of human platelets to Յ1 nM ␣-thrombin.…”
mentioning
confidence: 99%
“…DISCUSSION Thrombin has many substrates and inhibitors, including fibrinogen, prothrombin, protein C, antithrombin III, ␣ 2 -macroglobulin, and factors V, VII, XI, and XIII, that circulate at concentrations ranging from 30 nM to 10 M (26). By comparison, PAR1 is a rare substrate for thrombin with only 600 -1800 receptors present on the surface of each platelet (27,28). During the time period prior to clot formation, the prothrombinase complex on the surface of platelets generates 2-15 nM thrombin in whole blood (29).…”
Section: The C-terminal Region Of the Par1 Exodomain Modulates Thrombmentioning
confidence: 99%
“…22 PAR-1 receptors isolated from human platelets were used for this study. The inhibition constants (K i ) for the spirocyclic analogues are presented in Table 1.…”
mentioning
confidence: 99%